Pelatihan Analisis Sistem Informasi Rekapitulasi Penggunaan Jaringan Intra Pemerintah di Kementerian Komunikasi dan Informatika - Tarisa, Bunga; Sharyanto, Sharyanto (Yayasan Bina Internusa Mabarindo, 2025)
This training aims to enhance participants' understanding of the importance of information system analysis in the development of chat features for marketplace applications at PT. LinxChat. The main focus of the training is on mapping business process flows using Data Flow Diagram (DFD) and designing databases with Entity Relationship Diagram (ERD). In addition, participants are equipped with practical skills to analyze the current systems, identify issues, and design more efficient and structured system models to improve the performance of the marketplace application. The training results show a significant improvement in participants' understanding of fundamental system analysis concepts, their ability to accurately create DFDs and ERDs, and their readiness to implement technology-based solutions that support and accelerate the digitalization needs of modern marketplaces. The training also provides a deeper understanding of how to apply system analysis theory to solve the issues faced by companies in enhancing service quality and improving chat features for more efficient communication.